Early dissociation of face and object processing: A magnetoencephalographic study - Susac, Ana (Hum Brain Mapp, 2008)
The early dissociation in cortical responses to faces and objects was explored with magnetoencephalographic (MEG) recordings and source localization. To control for differences in the low‐level stimulus features, which are known to modulate early brain responses, we created a novel set of stimuli so that their combinations did not have any differences in the visual‐field location, spatial frequency, or luminance contrast. Differing responses to face and object (flower) stimuli were found at about 100 ms after stimulus onset in the occipital cortex. Our data also confirm that the brain response to a complex visual stimulus is not merely a sum of the responses to its constituent parts; the nonlinearity in the response was largest for meaningful stimuli. Hum Brain Mapp, 2009. © 2008 Wiley‐Liss, Inc.